Optimal growth conditions for avocado (Persea americana Mill.) seedlings using biofertilizer-based approach with biosurfactant diethanolamide palm olein and neem extract - Muhamad Sopian; Nurmayulis; Abdul H. Sodiq; Julio E. R. Rumbiak (Jurnal Ilmiah Pertanian, 2023)
Avocado is a much-loved fruit with high nutritional content. However, its current production has declined due to excessive and continuous use of chemical fertilizers. Biofertilizers can be applied to reduce the reliance on chemical fertilizers, promoting soil health and fertility by providing essential macro and micronutrients for better plant growth. This study aimed to determine the optimal dosage and method for the combined application of biofertilizer, biosurfactant diethanolamide (DEA) palm olein, and neem extract on avocado seedlings. The experimental design used was a factorial randomized complete block design with two factors. The first factor was the biofertilizer dosage (B) and the second factor was the application method (M). Results indicate that a 10 mL/L biofertilizer dosage, 5% DEA, and 35% neem extract show the best effects on plant height, leaf chlorophyll levels, stem diameter, and the number of avocado leaves. The application method of applying to the planting medium yields the best results for plant height, leaf count, and leaf chlorophyll levels. There was an interaction between treatments regarding plant height at 10 weeks after transplanting (WAT) and leaf count at 8 WAT. Biofertilizer application by pouring is recommended as an alternative to inorganic fertilizers for promoting healthy avocado seedling growth.